MENGEMBANGKAN POLITIK BERWATAK KERAKYATAN (STUDI ELABORASI NORMATIF-HISTORIS TERHADAP KONSEP UMMAH DALAM AL-QURAN) - Rohimin Rohimin (Universitas Islam Negeri Fatmawati Sukarno, 2015)
The Qur’an has a variety of concepts and offer of a problem, including in developing the political concept of Islam. This paper attempts to collaborate and offer the effort to develop the popular character of political Islam through normative-historical approach. This approach is done in order to know theoretically deductive and its implementation in the history of Islamic civilization, especially in matters relating to politics in Islam. To develop the necessary political popular character main instruments as development hubs. Instrumentation Islamic politics in an attempt to strengthen the political as a force of human development, enhancement, and preservation of human dignity as well as advocacy for the rights and duties of man. Strength and honor humanbeing can be realized in a religious political system that is framed by a political instrument pluralist and humanist